Counter-mapping platformization. Rethinking the spatial differentiation of platform control, labor relations and restaurant virtualization in proprietary markets for food-delivery - Yannick Ecker; Maximilian Lukowsky; Marius Wecker (Digital Geography and Society)
Living off financialization and crises of social reproduction, digital platforms play an increasing role as mediators of urban everyday life, productions of space and labor. Hence, subverting hegemonic narratives of pervasive platformization and bringing relationalities behind such care-less digital infrastructures back into focus has become a central challenge for critical analyses. In our contribution, we focus on proprietary markets for food delivery and develop a counter-strategy less explored in recent work on these forms of platform urbanism. By gathering and repurposing publicly-available platform data through counter-cartographies, we explore the spatial differentiation of platformized delivery logistics, labor relations and restaurant virtualization. We ground the need for such an approach in a theoretical discussion of recent work on platform urbanism and contrast it with narrower political economy perspectives that conceptualize platforms as proprietary markets. By using web-scraped data and public listings for the food aggregator platform Lieferando for Hamburg and Halle (Germany), we focus on restaurants as participating nodes in the digital platform's marketplace. Instead of offering a single alternative counter-narrative and counter-strategy, the contribution proposes to develop a dual perspective on the subsumption of labor relations under platformization and to complement academic interest in labor protests with a deeper concern for the food-delivery market as a site of conflict, accumulation and anti-competitive market practices.